Metallothionein isoform 3 expression in human skin, related cancers and human skin derived cell cultures. Issue 1 (5th January 2015) - Slusser, Andrea; Zheng, Yun; Zhou, Xu Dong; Somji, Seema; Sens, Donald A.; Sens, Mary Ann; Garrett, Scott H.
Highlights Skin is a target site of As+3 toxicity. Metallothionein-3 (MT3) is highly expressed in human skin. Skin-derived malignancies also expressed MT3. Suggested that MT3 is a major sulfhydryl source for dermal As+3 binding.